From State-Socialist Ambitions of Romanian Rural Indutrialisation to Post-Socialist Rural Deindutrialisation: Two Case Studies From Romania - Jucu, Ioan Sebastian (Eastern European Countryside, 2024)
The post-socialist changes in Romania’s communities profoundly changed the rural settlements with similar, contrasting and tensioned trends in the local rural development. The purpose of this study is to focus on the post-socialist rural dereliction. The paper unveils the post-socialist rural transformation in Romania, from the state-socialist interventions in rural industrialisation, to the post-socialist rural identity formation, using both quantitative and qualitative methods. During this process, two sampled case studies were thoroughly analysed, namely the Tomeşti and Margina communes – two rural settlements intensely industrialised under the former state-socialist political regime and with multiple consequences during the post-90s period in their local development. According to recent theories on economic changes reflected in local rural spatial development, the idea of rural dereliction remains peripheral and, at the same time, a hot-spot issue in the contemporary research on rural restructuring. In addition, recent theories on social and economic changes provide useful frameworks in studying the production of rural ruins. With post-socialist deindustrialisation, and under new post-90 capitalist rules in local rural development, rural communities faced multiple problems in creating their own post-socialist identity. Accordingly, this study highlights the local problems of rural deindustrialisation in the inner rural pattern of the investigated sites. While some rural communities embrace slow rural spatial regeneration trends, others remain ruined, marginalised and declined. The findings of the study confirm the presence of derelict abandoned places, thus highlighting the need for further proper interventions in local rural development, and for further fertile scientific dialogues to promote suitable strategies in Romanian rural regeneration on the local scale.